Team for change : a practitioner's guide to implementing change in the modern workplace. - Orr, Debra (Emerald Points Ser., 2021)
Team for Change: A Practitioner's Guide to Implementing Change in the Modern Workplaceaddresses the problems and multiple complexities of change process, focusing on the most intractable and unpredictable aspect of change: the human aspect.